Selective downregulation of retinoic acid-inducible gene I within the intestinal epithelial compartment in Crohn's disease - Funke, Benjamin; Lasitschka, Felix; Roth, Wilfried; Penzel, Roland; Meuer, Stefan; Saile, Maria; Gretz, Norbert; Sido, Bernd; Schirmacher, Peter; Autschbach, Frank (Inflammatory bowel diseases, 2011)
A defective innate immune response may contribute to the pathogenesis of Crohn's disease (CD) and ulcerative colitis (UC). Employing a global gene expression analysis, this study was aimed at identifying specifically regulated genes within the epithelial compartment in inflammatory bowel disease (IBD).The epithelial fraction of human ileal mucosa samples from surgical specimens was obtained by laser microdissection. Gene expression was examined by global expression profiling (n = 18, Affymetrix), quantitative reverse-transcription polymerase chain reaction (RT-PCR) (n = 35), immunoblot analysis (n = 9), and immunohistochemistry (n = 25).Global expression profiling revealed a pronounced downregulation of the retinoic acid-inducible gene I (RIG-I) within the epithelial layer of the ileum in patients with CD but not with UC. The downregulation of RIG-I was confirmed by quantitative RT-PCR, immunoblot analysis, and immunohistochemistry.Epithelial downregulation of RIG-I, a known pattern recognition receptor for viral components, might contribute to alterations of the innate mucosal immune response, particularly in CD. (Inflamm Bowel Dis 2011;)
Gesehen am 29.06.2023